2017
DOI: 10.1111/apha.12981
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of histamine receptor H3 alters adaptation to sudden darkness and monoamine levels in the zebrafish

Abstract: Our results show that HRH3 knockout larvae adapt faster to sudden darkness, suggesting a role for this receptor in regulating responses to changes in the environment. The decreased levels of dopamine and serotonin provide the first direct evidence that knockout of HRH3 alters these systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 77 publications
(175 reference statements)
6
16
0
Order By: Relevance
“…Mouse and human expression analyses have shown that the mammalian histamine H3 receptor is expressed in the cerebral cortex, thalamus, hypothalamus, basal ganglia, hippocampus and amygdala 6 . In zebrafish larvae and juveniles, strong hrh3 expression has been observed in the telencephalon, with moderate expression levels in the hypothalamus, thalamus and optic tectum 25 . To assess the potential role of the hrh3 receptor in aggression, we first mapped hrh3 distribution in the adult zebrafish brain (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse and human expression analyses have shown that the mammalian histamine H3 receptor is expressed in the cerebral cortex, thalamus, hypothalamus, basal ganglia, hippocampus and amygdala 6 . In zebrafish larvae and juveniles, strong hrh3 expression has been observed in the telencephalon, with moderate expression levels in the hypothalamus, thalamus and optic tectum 25 . To assess the potential role of the hrh3 receptor in aggression, we first mapped hrh3 distribution in the adult zebrafish brain (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…To assess the potential role of the hrh3 receptor in aggression, we first mapped hrh3 distribution in the adult zebrafish brain (Figure 1). Similar to larvae and juveniles, 25 hrh3 expression is limited to discrete brain areas and cell populations with the strongest expression in the telencephalon. Dorsal telencephalic subregions showed very strong signals, especially in the medial and lateral zone of the dorsal telencephalic area (Dm and Dl; Figure 1A‐C), regions that are considered homologous to the mammalian amygdala and hippocampus respectively 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Genetic approaches for the modelling of physiological mechanisms, but also of human diseases, are mirrored by numerous publications in Acta Physiologica (Oxf.) . Genetically induced alterations of proteins such as membrane receptors or ion channels have been applied to evaluate the contribution of the respective protein to the normal physiological function, or its potential role in the pathogenesis of diseases .…”
mentioning
confidence: 99%
“…. Genetically induced alterations of proteins such as membrane receptors or ion channels have been applied to evaluate the contribution of the respective protein to the normal physiological function, or its potential role in the pathogenesis of diseases . The combination of more traditional physiological models with genetic models opened up new possibilities in research .…”
mentioning
confidence: 99%
“…Puttonen et al (this issue) report behavioural features and abnormalities of zebrafish lacking the histamine H3 receptor, which regulates the release of several neurotransmitters, including GABA, glutamate, histamine, serotonin, noradrenaline and dopamine . Despite normal morphological development, mutant larvae show faster locomotor adaptation to sudden darkness than control larvae, whereas there are no differences in basic locomotor activity during daytime and night.…”
mentioning
confidence: 99%